The study of curtain wall paneling installation in Malaysia / Nur Anis Asneeda Mohamed and Norehan Mohd Noor - Mohamed, Nur Anis Asneeda; Mohd Noor, Norehan (2019)
Façade gives the building an exquisite design which distinguishes the building form each other. Nowadays, Curtain wall systems a commonly used for modern buildings, and it becomes a major investment in construction. Compared to reinforced concrete structure, curtain wall systems are new technology in the construction industry. This research focus on the type and analysis of suitable curtain wall, maintenance and their life span for high rise building. The curtain wall systems nowadays, even the simpler types are far more sophisticate products than their early counterparts, through many of experience and development have eliminated the major difficulties of the pioneering designs, resulting the better products.